Occupational Safety and Health Risk Evaluation in Container Handling Operations Using the HIRADC Method: A Case Study at PT. Kaltim Kariangau Terminal, East Kalimantan, Indonesia - Arif Fuddin Usman; Andi Ningrat; Muslihati Muslihati; Andi Rachmianty; Rusnaedi Rusnaedi (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Occupational safety and health is a critically important aspect of container loading and discharging operations at ports, encompassing efforts to create a safe, healthy work environment and prevent workplace accidents and work-related diseases. Objective: This study aims to analyze the application of occupational safety and health in the process of loading and discharging containers at PT. Kaltim Kariangau Terminal. Methods: This study uses the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) method. Results: The results of the risk level assessment before control indicate a High Risk level of 9 risks (23.1%), a Moderate Risk level of 17 risks (43.6%), and a Low Risk level of 13 risks (33.3%). After control, the High Risk level is reduced to 0 risks (0%), with no remaining high-risk work activities; the Moderate Risk level is 8 risks (20.6%); and the Low Risk level is 31 risks (79.4%). To address these hazards and risks, PT. Kaltim Kariangau Terminal has implemented risk controls, namely substitution, engineering controls, administrative controls, and personal protective equipment. Conclusion: The findings demonstrate that systematic hazard identification and hierarchical risk control, when applied rigorously to RTG crane operations in container terminals, can deliver measurable reductions in worker exposure to life-threatening risks and provide a replicable OSH management model for the Indonesian port sector.